Building the character of unity through a STEAM approach in elementary schools - Yayuk Hidayah; Rossi Iskandar; Intan Kusmayanti; Nadya Putri Saylendra (Geuthèë Institute, Aceh, 2023)
Using the STEAM approach in civics education in elementary schools is an idea to update students' skills in building a unified character by using STEAM in Civics. In particular, this study aims to analyze, study and explore the building of the character of unity using the STEAM approach in civics education in elementary schools. This study uses a qualitative literature study. After conducting the study, the researcher can confirm that building the character of unity in civics education in Elementary Schools by using the STEAM approach can be emphasized in two stages, namely 1) Strengthening civics education in STEAM-based Elementary Schools, 2) The character of the 3rd precept through STEAM in civics education in Elementary Schools . The conclusion of this study is that the STEAM approach in PPKn in Elementary Schools will begin to be applied, especially in facing the new normal era in the world of education.